Effects of steroids on NMDA receptors and excitatory synaptic transmission in neonatal motoneurons in rat spinal cord slices - Abdrachmanova, G; Chodounská, H; Vyklický, L (The European journal of neuroscience, 2001)
The effect of steroids on NMDA receptors and excitatory postsynaptic transmission was studied in fluorescence-labelled motoneurons in thin spinal cord slices. In outside-out patches, NMDA-induced responses were potentiated by 79% in the presence of 20-oxopregn-5-en-3beta-yl sulfate (PS), while in the presence of 20-oxo-5alpha-pregnan-3alpha-yl sulfate (3alpha5alphaS) and 20-oxo-5beta-pregnan-3alpha-yl sulfate (3alpha5betaS) they were diminished by 57% and 66%, respectively. PS and 3alpha5betaS had no effect on the amplitude of single NMDA receptor channel openings, however, both compounds altered relative distribution of the openings to individual conductance levels. In control cases, the most frequent openings of the NMDA receptor channels were at the 70 pS conductance level, while in the presence of PS or 3alpha5betaS, the most frequent openings were at the 55 pS conductance level. Analysis of the mean current transferred by NMDA receptor channel openings at individual conductance levels indicated that in the presence of PS, the mean current induced by 55 pS conductance openings was significantly increased. In the presence of 3alpha5betaS, the mean currents induced by 55 pS and 70 pS conductance openings were significantly decreased. The amplitude of NMDA receptor-mediated EPSCs was potentiated by 54% in the presence of PS and the deactivation kinetics slowed. Neither the amplitude nor the kinetics of NMDA receptor-mediated EPSCs was significantly changed in the presence of 3alpha5betaS. The results of our experiments indicate that neurosteroids affect NMDA receptors in motoneurons. The effect appears to be influenced by the receptor subunit composition.
Keywords: Animals; novorozená zvířata; Motor Neurons; Rats, Wistar; Spinal Cord; Electrophysiology; In Vitro Techniques; Animals, Newborn; techniky in vitro; Excitatory Postsynaptic Potentials; mícha; Algorithms; Receptors, N-Methyl-D-Aspartate; steroidy; Patch-Clamp Techniques; motorické neurony; excitační postsynaptické potenciály; nervový přenos; Synaptic Transmission; algoritmy; krysa rodu Rattus; elektrofyziologie; receptory N-methyl-D-aspartátu; zvířata; metoda terčíkového zámku; Rats; Steroids; potkani Wistar